The Scaffolding Activities of International Returnee Executives: A Learning Based Perspective of Global Boundary Spanning. (13th March 2017) - Roberts, Michael J.D.; Beamish, Paul W.
Abstract: This study contributes to the literature on global boundary spanning by taking a learning perspective that positions the boundary spanner as an active change agent. Grounded in a practice‐based theory of knowledge, it considers boundary spanning as the negotiation of knowledge and relationships across fields of practice. We argue that global boundary spanning is a long‐term commitment to help internal members become aware of foreign knowledge practices, see these practices as valuable, and adopt them internally. We frame the activities of the boundary spanner within a scaffolding framework that theorizes boundary spanning as a combination of ability, persistent willingness, and opportunity. Here scaffolding refers to the cognitive, relational, and material supports enacted by boundary spanners that facilitate organization members' engagement in practices that allow for the awareness, capacity building, and commitment to adoption of foreign practices. We draw on interviews from international returnee managers employed in large Korean financial firms.